Faktor-Faktor Sosial Ekonomi yang Mempengaruhi Pendapatan Petani Karet di Desa Layuh Kecamatan Batu Benawa Kabupaten Hulu Sungai Tengah - Herni Agustina; Miranda Romaully Br. Sitanggang; Rum Van Royensyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
Rubber is an export commodity that is able to contribute to efforts to increase Indonesia's foreign exchange. Rubber plants are one of the plantation commodities that occupies a quite outstanding position as a source of non-oil foreign exchange for Indonesia so that it has bright prospects. This study aims to determine how much influence the rubber farmers' income has on age, education, family dependence, and the number of trees and which factors have the most significant control. The time of the study was carried out from March to May 2018. The data used in this study were primary data and secondary data. Primary data obtained by direct interview census, at the research location on the respondents of rubber farmers as a whole amounting to 61 people. Adjusted R2 value is 0.422, and this indicates that 42.2% of income can be explained by the variables of age, education, dependents of the family, number of trees while 57.8% is influenced by other variables which may not be included in the regression model mentioned in the study. The most significant factor is the number of trees/hectare with a regression coefficient of 0.582 with a significance of 0,000.